(untitled) (Communications in Mathematical Research, 2021)
In this paper, we investigate the eigenvalue problem of forward-backward doubly stochastic differential equations with boundary value conditions. We show that this problem can be represented as an eigenvalue problem of a bounded continuous compact operator. Hence using the famous Hilbert-Schmidt spectrum theory, we can characterize the eigenvalues exactly.